2014
DOI: 10.1186/s12916-014-0121-6
|View full text |Cite
|
Sign up to set email alerts
|

Ancestral exposure to stress epigenetically programs preterm birth risk and adverse maternal and newborn outcomes

Abstract: BackgroundChronic stress is considered to be one of many causes of human preterm birth (PTB), but no direct evidence has yet been provided. Here we show in rats that stress across generations has downstream effects on endocrine, metabolic and behavioural manifestations of PTB possibly via microRNA (miRNA) regulation.MethodsPregnant dams of the parental generation were exposed to stress from gestational days 12 to 18. Their pregnant daughters (F1) and grand-daughters (F2) either were stressed or remained as non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
147
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 126 publications
(164 citation statements)
references
References 63 publications
(91 reference statements)
14
147
0
3
Order By: Relevance
“…Our previous work showed that http multi-generational experience of recurrent PNS accumulates across generations and sensorimotor impairments in later generations exceed the effects of PNS in the first generation (Erikson et al, 2014;Yao et al, 2014). Contrary to such sensorimotor deficits, we propose that some essential cognitive functions may reveal adaptive changes of stress coping in multi-generational prenatal stressed (MGPNS) rats.…”
Section: Introductionmentioning
confidence: 65%
“…Our previous work showed that http multi-generational experience of recurrent PNS accumulates across generations and sensorimotor impairments in later generations exceed the effects of PNS in the first generation (Erikson et al, 2014;Yao et al, 2014). Contrary to such sensorimotor deficits, we propose that some essential cognitive functions may reveal adaptive changes of stress coping in multi-generational prenatal stressed (MGPNS) rats.…”
Section: Introductionmentioning
confidence: 65%
“…They linked their findings to epigenetic regulation of the placenta and other key tissues, providing a potential mechanism for inter-generational transmission of stress. 61 This study has a number of strengths and limitations. The primary limitation is the sample size, which is, in part, due to the fact that we restricted the design to only African Americans with spontaneous PTB prior to 34 weeks gestation and uncomplicated controls.…”
Section: Discussionmentioning
confidence: 99%
“…Yao ve arkadaşları tarafından yapılan çalışmada, dişi fareye gebeliğin 12-18. günleri arasında kronik stres uygulanmasının F1, F2 ve F3 farelerde gebelik süresinde azalma, gebelik döneminde kilo alımı ve kan glukoz düzeyinde artış gözlenmiştir (21). Stres uygulaması ayrıca yavrularda büyüme geriliğine ve davranış bozukluklarına yol açarken, F2 annelerde beyin ve uterusta miR-200 ailesine ait miRNA'ların ifadelerinde değişiklikler saptanmıştır (21). Yapılan çalışmalarda, paternal stres sonucu sperm hücrelerinde oluşan epigenetik düzenlemelerin de sonraki jenerasyonlara aktarılarak yavrularda stres ile ilişkili fenotiplerin ortaya çıkmasına neden olduğu saptanmıştır (39).…”
Section: şEkil 4 Farede Agouti Lokusunun Metilasyon Değişiklerinin Kunclassified